2002
DOI: 10.1046/j.1365-2672.2002.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial susceptibility changes and T-OMP shifts in pyrithione-passaged planktonic cultures of Pseudomonas aeruginosa PAO1

Abstract: Aims: The aim of this study was to determine whether passaging Pseudomonas aeruginosa PAO1 with sub-MICs of the pyrithione biocides results in both the induction of decreased susceptibility towards these antimicrobials and associated outer membrane profile changes. Methods and Results: Previous work by this group has shown that it is possible to induce susceptibility changes towards the isothiazolone biocides in Ps. aeruginosa PAO1 by successive passages in the presence of increasing sub-MICs of biocide. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The MIC changed from 4 to 8 and 60 to 69 g/mL, respectively. However, Abdel Malek et al (2002) reported ZnPT induced resistance to increase MIC to 25 g/mL from an initial value of 4 g/mL. In that study ZnPT resistance resulted in cross resistance towards NaPT and caused the MIC of NaPT to change from 30 to 115 g/mL.…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…The MIC changed from 4 to 8 and 60 to 69 g/mL, respectively. However, Abdel Malek et al (2002) reported ZnPT induced resistance to increase MIC to 25 g/mL from an initial value of 4 g/mL. In that study ZnPT resistance resulted in cross resistance towards NaPT and caused the MIC of NaPT to change from 30 to 115 g/mL.…”
Section: Resultsmentioning
confidence: 88%
“…Biocide resistance in bacteria is known to involve several mechanisms (Loughlin et al 2002;Abdel Malek et al 2002, 2009Russell 2003) thus when a small increase in MIC is observed it indicates the possible disabling of one biocide target (Gilbert and MacBain 2001). Cross-resistance to BIT on the other hand, showed significant (p < 0.05) three-fold increase in the MIC from 32 to 85 g/mL (Table II).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations